APLIKASI SIMULASI PROBABILISTIK UNTUK MEMPREDIKSI KETERSEDIAAN BARANG PADA TOKO REMAJA PONSEL MENGGUNAKAN METODE MONTE CARLO BERBASIS WEB - Istara Nadia; Husaini Husaini; Laila Qadriah; Zulfa Razi (Jurnal Sains Riset, 2023)
The youth mobile shop is a small and medium business located in pasi lhok village, Kembang Tanjong subdistric, Pidie district, Aceh province, the youth mobile shop sells various types of cellphones including Samsung, Xiaomi, Oppo, Asus, Lenovo, Huawei, and so on. With the right sales quantity planning, business actors in mobile youth shops will be able to predict well the possible in the future. Monte carlo is not a type of simulation, but rather a technique used for simulation. This method is quite simple in describing or solving various problems,including in using the programs. The monte carlo method can find out the average number of requests for goods and helps determine the percentage of product sales in the store so that it can be used as a consideration in making strategies for sales more effective.Keywords : Application, Probabilistic, Simulation, Availability Prediction, Monte carlo method